2020
DOI: 10.1101/2020.08.30.273979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ebselen derivatives are very potent dual inhibitors of SARS-CoV-2 proteases - PLproand Mproin in vitro studies

Abstract: Proteases encoded by SARS-CoV-2 constitute a promising target for new therapies against COVID-19. SARS-CoV-2 main protease (Mpro, 3CLpro) and papain-like protease (PLpro) are responsible for viral polyprotein cleavage - a process crucial for viral survival and replication. Recently it was shown that 2-phenylbenzisoselenazol-3(2H)-one (ebselen), an organoselenium anti-inflammatory small-molecule drug, is a potent, covalent inhibitor of both the proteases and its potency was evaluated in enzymatic and anti-viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 48 publications
2
57
1
Order By: Relevance
“…[39] Experimental and in silico studies have been carried out to find new Mpro and PLpro inhibitors, as well as, to explain the mechanisms of enzyme inhibition at the molecular and atomic level. [23,[40][41][42][43] Recent studies have suggested that EbSe interacts in the active site of the Mpro and PLpro and could react with the Cys145 and Cys111, respectively, leading to a Se-S bond formation, inhibiting the proteases, as previously demonstrated in vitro. [9,22] In addition, an in silico study has indicated that EbSe can bind with high probability to a second binding site of Mpro, located between the II and III domains (residues: Gln107, Pro108, Ile200, Val202, His246, Phe294), besides the catalytic site.…”
Section: Introductionmentioning
confidence: 62%
“…[39] Experimental and in silico studies have been carried out to find new Mpro and PLpro inhibitors, as well as, to explain the mechanisms of enzyme inhibition at the molecular and atomic level. [23,[40][41][42][43] Recent studies have suggested that EbSe interacts in the active site of the Mpro and PLpro and could react with the Cys145 and Cys111, respectively, leading to a Se-S bond formation, inhibiting the proteases, as previously demonstrated in vitro. [9,22] In addition, an in silico study has indicated that EbSe can bind with high probability to a second binding site of Mpro, located between the II and III domains (residues: Gln107, Pro108, Ile200, Val202, His246, Phe294), besides the catalytic site.…”
Section: Introductionmentioning
confidence: 62%
“…However, within our assay we did not observe activity for ebselen, a small molecule with demonstrated in vitro activity against purified SARSpg. 6 reports showing that ebselen is highly reactive and readily forms selenosulfide bonds with numerous proteins including the SARS-CoV-2 papain-like protease (PLP) [19,[31][32][33].…”
Section: Compound Rescue Of Transfected 3clpro Cytotoxicity Mimics the Results Obtained With Live Virusmentioning
confidence: 99%
“…In this group, the main direction seems to be focused on the peptide scaffolds [30]. There are also other proposals for nonpeptide, covalent inhibitors, such as ebselen [37], its derivatives [31], and disulfiram [38]. In the case of the peptide inhibitors, the covalent bond is formed with one of the amino acids of the catalytic triad-Cys111.…”
Section: Resultsmentioning
confidence: 99%
“…The search for PLpro inhibitors has already begun. So far, most studies focus on trying to utilize previously developed noncovalent SARS-CoV inhibitors or their derivatives [7,24,29] or to design specific, covalent inhibitors [30,31]. However, covalent protease inhibitors come with risks of toxicity due to high reactivity and, in some cases, low selectivity and nonspecific binding off the target [32][33][34].…”
Section: Introductionmentioning
confidence: 99%